SOSIALISASI BAHAYA NARKOBA, PSIKOTROPIKA DAN ZAT ADITIF (JAMUR TLETHONG) - Agus Taufiq (UII, 2015)
Drugs and narcotics are the substances that used in the medical world to various treatments, but over time turned it is turned into a threat and had a very bad effect onhealth and mental when it is used in accordance with the dosage and proper purpose.Over time, more and more type of drugs encounter many developments. Several types of fungal are into the class of drugs. One of them is “Jamur Tlethong” or known as amagic mushroom. Jamur Tlethong is a type of fungus that can cause hallucinations.Today, this magic mushroom is widely abused, especially by young generations with non-medical purposes in order to change the mood, change the perception of themselves orthe world around, gain sensation and experience the “new” and “romantic” as well as toimprove the ability of a specific function in the social and sexual. This magic mushroom grows in cow manure.Dusun Klumprit II is a dusun that located in Wukirharjo, Prambanan, District Sleman and Yogyakarta Province. The majority of the residents of Dusun Klumprit II isbreeding. The development of Magic mushroom in this dusun is high. Concerns about the spread of this mushroom arose due to the public ignorance of the type and thedangers of Drugs, Psychotropic and addictive substance is necessary needed for the residents of Dusun Klumprit II, particularly the knowledge about Jamur Tlethong ormagic mushroom. After having held the door-to-door socialization, the residents ofDusun Klumprit II know the dangers of magic mushroom and the residents will be more careful to not consume the magic mushrooms.